(untitled) (International journal of medical sciences, 2026)
this article examines the significance of the service sector in the modern economy and post-industrial society. It analyzes the concepts of “service” and “service sector,” highlighting the main economic and social functions of the sector. Economic functions include the creation of added value, provision of services to production processes, and reproduction of the workforce. Social functions involve employment of the population, effective organization of leisure time, and meeting various service needs. The article also evaluates the development prospects of the service sector in Uzbekistan and its potential to become a leading sector in a post-industrial society.